2001
DOI: 10.1046/j.1460-2695.2001.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behaviour and lifing of two single crystal superalloys

Abstract: A model has been developed to predict the high temperature cyclic life of single crystal superalloys RR2000 and CMSX‐4 under conditions of creep and fatigue. A combined creep–fatigue model is used, although it is found that failure always occurs by creep or fatigue separately, and that creep–fatigue interaction has a minor influence. Microstructural investigation of a series of interrupted high‐ and low‐frequency tests are presented, these are combined with the results of a series of interrupted creep tests to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 27 publications
4
61
0
Order By: Relevance
“…The criterion of the transition between stage-I and stage-II cracking were also studied [6,17,18,20,23]. Stage-I cracking prefers low temperature, high frequency, high SIF and vacuum condition, while stage-II cracking prefers high temperature, low frequency, low SIF and oxidizing atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The criterion of the transition between stage-I and stage-II cracking were also studied [6,17,18,20,23]. Stage-I cracking prefers low temperature, high frequency, high SIF and vacuum condition, while stage-II cracking prefers high temperature, low frequency, low SIF and oxidizing atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports were already published describing anisotropic behavior of single crystal superalloys: tensile strength [2,3], fatigue strength [4][5][6], crack propagation behavior [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In regard to crack propagation behavior of single crystal superalloys, it is well known that cracks tend to propagate on {111} slip planes at low temperature, while cracks usually propagate normal to loading direction independent of crystal orientation at high temperature [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…6,7) That is to say, the high-temperature fatigue resistance of alloys was generally reduced with increasing temperature and decreasing frequency due to an interaction between creep and fatigue. 6,7) For this reason, it was suggested that, in the present work, the testing temperatures, 573 and 673 K, were still too low or the loading frequencies, 20 and 2 Hz, were too high to generate any detrimental creep damage during cyclic loading. Hence, time-dependent mechanisms such as creep or others did not significantly contribute to the fatigue failures for the given alloys at 573 and 673 K except for H900 condition tested at 673 K.…”
Section: Effect Of Frequency On the Fatigue Behaviormentioning
confidence: 99%
“…The occurrence of timedependent creep mechanism in high-temperature fatigue has been known to be a function of temperature and loading frequency. 6,7) At higher temperatures and lower loading frequencies, creep damage would readily take place and cause premature fatigue failure as compared with timeindependent fatigue failure mechanisms. 6,7) That is to say, the high-temperature fatigue resistance of alloys was generally reduced with increasing temperature and decreasing frequency due to an interaction between creep and fatigue.…”
Section: Effect Of Frequency On the Fatigue Behaviormentioning
confidence: 99%
See 1 more Smart Citation